Enhancing Students’ Ecological Literacy Through Place-Based Pedagogy in Indonesian EFL Classroom - Amelia Kurniasari Farouk; Sary Silvhiany; Rita Inderawati (Universitas Pendidikan Mandalika, 2026)
Ecological literacy has emerged as a critical competency in the face of growing environmental challenges, yet English language instruction in many Indonesian EFL contexts continues to address ecological issues in decontextualized and abstract ways. Previous studies on place-based pedagogy (PBP) have largely concentrated on science education or Western school settings, leaving a significant empirical gap regarding its application in Indonesian secondary EFL classrooms. This study examined how place-based pedagogy enhances Grade XI students’ ecological literacy at senior high schools Palembang, South Sumatra, within a Participatory Action Research (PAR) framework. A mixed-methods design was employed involving 35 Grade XI students and one English teacher across eight instructional meetings. Quantitative data were collected through pre-test and post-test instruments measuring students’ reading ecological literacy and ecological knowledge, and analyzed using paired-sample t-tests. Qualitative data were gathered through classroom observations and semi-structured interviews with nine selected students and the English teacher, and analyzed thematically following Braun and Clarke’s (2006) framework. Results revealed statistically significant improvements in both reading ecological literacy (t(34) = −18.71, p < .001) and ecological knowledge (t(34) = −22.54, p < .001). Thematic analysis identified four student-centred mechanisms: real-life relevance, emotional engagement, improved ecological understanding, and active participation. Teacher findings demonstrated that collaborative PAR processes supported professional development, enabling the teacher to independently incorporate environmental themes into formal examinations in the subsequent academic year. This study concludes that place-based pedagogy constitutes an effective and contextually responsive approach for integrating ecological literacy into EFL instruction at the secondary school level in Indonesia.